The fallacy of the natural rate of interest and zero lower bound economics - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper provides a critique of zero lower bound (ZLB) economics which has become the new orthodoxy for explaining stagnation. ZLB economics is an extension of pre-Keynesian economics which attributes macroeconomic dysfunction to rigidities and market imperfections. The ZLB is the latest rigidity in that pre-Keynesian tradition. The paper argues negative nominal interest rates, even if feasible, may be unable to remedy Keynesian demand shortage unemployment, and might even aggravate the problem. That is because there exist non-reproduced assets whose return dominates that of investment, and saving may also increase in response to negative rates. Consequently, there may be no natural rate of interest.
Keywords: E0; E10; E12; E20; E40; E50; 330; zero lower bound (ZLB); natural rate of interest; non-reproduced assets; stagnation; New Keynesianism; nominal rigidities